The Chinese EPOCH Measure of Adolescent Wellbeing: Further Testing of the Psychometrics of the Measure - Zeng, Guang; Kern, Margaret L. (Frontiers in Psychology, 2019)
Given the enormous population of Chinese-speaking people worldwide, it is important to establish measures of adolescent wellbeing with adequate evidence for reliability and validity. The EPOCH Measure of Adolescent Wellbeing assesses five positive psychological characteristics (engagement, perseverance, optimism, connectedness, and happiness). An initial study with the English version of the measure found support for a five-factor structure, and evidence for internal reliability, convergence with other wellbeing measures, and divergence across factors and with unrelated constructs. An initial study translated the measure into Chinese and found support for the factor structure of the measure. To further test the measure’s psychometrics, data were collected from 11 Chinese student samples (N = 17,854) from several regions of China. All students completed the EPOCH Measure, along with a variety of other measures. In cases where measures overlapped, samples were combined, with relevant sub-sets used to examine convergent and divergent patterns. Confirmatory analyses supported the five-factor structure and factors were internally reliable, but consistency over time was low. The five factors were more strongly correlated with other wellbeing factors than with illbeing factors. While some correlations demonstrated expected convergent and divergent patterns with other constructs, there was also considerable deviations from expected patterns. Norm values specific to the Chinese version of the measure are provided. The study supports the EPOCH Measure as a useful cross-sectional tool for measuring adolescent positive functioning, but additional consideration of cross time stability, change, and correlations with other constructs is needed.